Akar Qur’ani dan Perkembangan Ilmu Kalam : Dalam Sejarah Pemikiran Teologi Islam Klasik Sunni Global Kontemporer - M. Faiz Al Ansori; Clara Angelika (Taqrib : Journal of Islamic Studies and Education, 2026)
Kalam, a discipline of Islamic theology that integrates Qur'anic revelation with rational reason, has deep roots in Qur'anic teachings that emphasize monotheism, the attributes of God, and belief in prophethood and the Last Day. This article explores the Qur'anic foundations of Kalam and its history of emergence as an intellectual response to internal (such as the debates over qadar and the caliphate) and external (the influence of Greek philosophy and other religions) challenges in the early Islamic period. Using a qualitative approach based on literature review and textual analysis, this study finds that Kalam not only served as a bastion of faith (aqidah) but also as a catalyst for the evolution of Islamic thought, from the rationalist Mu'tazilite school to the balanced Ash'arites.